Changing challenges and crisis management methods within a stable rule of law: Hungary's constitutional response to the challenges of the 21st century - Simicskó, István (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The defence and security of Hungary is a national matter, on which the survival and development of the nation, the community and individual rights are based. It is a priority objective to enhance the security of the country and the nation and to fulfil Hungary's obligations in the international alliance system. In view of this, the continuous functioning of the State organisation, the performance of security and defence tasks and, if necessary, the restriction of citizens' rights within the constitutional framework must be ensured with adequate operational efficiency and in full compliance with the guarantees of the rule of law, even in the context of the peacetime and special legal order periods defined in Fundamental Law, and in the course of coordinated preparation and defence against various threats, harmful, influencing and offensive behaviour based on natural and civilizational events and human actions.The security challenges of the 21st century and the rapidly changing environment call for a new regulatory framework that can provide a flexible, transparent way in which defence and security system can operate in peacetime and in times of special legal order. A framework for the preparation of state bodies needs to be provided and measures along which the competent bodies can act in a period of special legal order need to be defined in detail, so that the country's functioning and its legal order can return to normal as soon as possible after the reason of the special legal order has been lifted. It is an important pillar of stability of a democratic state that the freely elected legislature, Parliament, determines the content and the form of cases in which it is possible to derogate from the general rules. There are different types of special status, so the concentration of power should be implemented only to the extent strictly necessary to resolve the situation, in accordance with the principle of proportionality. The institutions of special legal order are therefore institutions of a temporary and urgent nature which can be deployed as ultima ratio of state instruments in a situation of necessity, provided that their constitutional conditions are met.
Keywords: special legal order, qualified period